Langkah Strategis Meningkatkan Pemahaman Siswa tentang Pendidikan untuk Pembangunan Berkelanjutan Melalui Pembelajaran Berbasis Masalah - Bawadi, Titik Handayani; Ahman, Eeng; Kurniawati, Susanti; Sutarni, Nani; Prasetio, Bayu (Jayapangus Press, 2025)
Education in Indonesia faces major challenges in the 21st century, particularly regarding the gap in education quality between urban and rural areas and the low adaptability to new technologies and learning methods. Education for Sustainable Development (ESD) and Problem-Based Learning (PBL) are considered potential approaches to address these challenges. This research aims to explore the effectiveness of PBL in improving students' understanding of ESD concepts. The method used is a literature study by analyzing various relevant previous studies. The results showed that PBL is effective in improving students' understanding of sustainability issues through active and collaborative learning. PBL applied to science subjects, such as Biology and Chemistry, as well as social, such as Economics, has been shown to improve critical thinking, creative, and problem-solving skills. In the context of ESD, students who learn through PBL are better able to integrate sustainability principles in practicum activities and group discussions. Several studies have also shown that the use of ESD-based modules in PBL helps improve student learning outcomes, both in theoretical understanding and applicative skills. However, these studies also identified challenges in implementation, such as students' low science literacy, limited integration of sustainability principles, and the lack of knowledge of sustainability.